Epidemiological characteristics of myopia among school-age children before, during, and after the COVID-19 pandemic: a cohort study in Shenzhen, China - Mu, Jingfeng; Zhong, Haoxi; Jiang, Mingjie; Yang, Weihua (Frontiers in Medicine, 2024)
Objectives To evaluate the epidemiological characteristics of myopia among school-aged children before, during, and after the coronavirus disease (COVID-19) pandemic. Methods A total of 848,697 students aged 6–15 years from 786 primary and secondary schools in Shenzhen, China, were randomly selected as research subjects. We conducted annual myopia screenings from 2019 to 2022. 2019 was considered before the COVID-19 pandemic, 2020 as during the pandemic, and 2021 and 2022 as after the pandemic. Demographic characteristics, visual acuity, and spherical equivalent refraction (SE) were collected. Results During the 4-year follow-up period, the uncorrected visual acuity (UCVA) of the study subjects progressed following a trend of −0.18 ± 0.30D (−0.17 ± 0.29D for boys, −0.21 ± 0.32Dfor girls) (p < 0.001). Those students who were in grade 4 aged 9–10 years at the baseline examination showed the greatest decline in visual acuity (0.23). The SE of the study subjects progressed following a trend of −1.00 ± 1.27D (−0.96 ± 1.25D for boys, −1.05 ± 1.31D for girls) (p < 0.001). The students who were in grade 5 aged 10–11 years at the baseline examination showed the greatest decline in SE (1.15D ± 1.22, p < 0.001). The prevalence of myopia (UCVA<5.0 and SE < –0.50D of any eye) increased by 28.2% (27.0% for boys and 29.8% for girls). Those students who were in grade 2 aged 7–8 years at the baseline examination showed the greatest increase in myopia prevalence (37.6%, p < 0.001). During the COVID-19 pandemic, the subjects’ visual acuity and SE measurements decreased by −0.05 ± 0.19 (p < 0.001) and − 0.36 ± 0.89D (p < 0.001) respectively, and the prevalence of myopia increased by 11.3% (10.6% for boys and 12.2% for girls) (p < 0.001). The 3-year cumulative incidence of myopia for non-myopic grade 1 aged 6–7 years students with baseline SE of ≥1.00D, ≥ 0.50D and < 1.00D, ≥0D and < 0.50D, and ≥ −0.50D and < 0D were 6.8, 24.8, 39.0, and 48.1%, respectively. Conclusion During the COVID-19 pandemic, the SE of school-aged children showed myopic drift and decreased visual acuity. Myopia progressed faster among girls than among boys in the same grades. The risk of myopia among school-aged children persisted even after the home quarantine of the COVID-19 pandemic was lifted.